Prevalence of Antibiotic Resistant Aeromonas and Molecular Identification of Aeromonas hydrophila Isolated from Some Marketed Fish in Egypt - Morshdy, Alaa Eldin M.A.; Abdelhameed, Nehal Samir Ahmed; El Bayomi, Rasha M.; Abdallah, Karima (Journal of Advanced Veterinary Research, 2022)
Aeromonas hydrophila, is an important foodborne bacterial disease in the aquaculture. The present study aimed to investigate the prevalence of Aeromonas species, virulence genes associated in A. hydrophila and to determine the antimicrobial susceptibility of Aeromonas spp. isolated from fish samples (tilapia, mugil, tuna, saurus, pagrus and shrimp) collected from Zagazig city markets, Sharkia Governorate, Egypt. Aeromonas spp. was isolated with a percentage of 39.3% of all examined fish samples. Four Aeromonas species (A. hydrophila, A. caviae, A. fluvials and A. sobria) were isolated from the tested fish samples (12%, 15.3%, 2.7% and 9.3%, respectively). A. hydrophila was only isolated from Tilapia, Saurus and Shrimp samples (16%, 28% and 28%, respectively). Aerolysin (aerA) and haemolysin (ahh1) were expressed in 100% and 75% of the A. hydrophila isolates. Antibiotic susceptibility testing of Aeromonas spp. revealed marked resistant for testing antibiotics; Ampicillin (100 %), Erythromycin (100 %), Tetracycline (83.3 %), Sulphamethoxazol (75 %), Cefotaxime (50 %) and Cephalothin (50 %). Dipping of Nile tilapia in lemon juice 5% for 2 h reduced A. hydrophila counts by 0.45 log cfu/g (64.44%). In conclusion, the present study confirms contamination of fish by Aeromonas spp. Immersion of fish in in lemon juice 5% is an efficient policy for reducing A. hydrophila in fish.